Does split nitrogen application increase garlic yield and quality? - Besen, Marcos Renan; Ogawa, Juliano Masahiko; Ribeiro, Ricardo Henrique; Guginski-Piva, Claudia Aparecida; Piva, Jonatas Thiago (Scientia Agraria Paranaensis, 2020)
Nitrogen (N) fertilization is essential for obtaining high garlic yields and satisfying commercial requirements for bulb diameter. However, excess nitrogen may favor the development of lateral shoots. This study aimed to examine the effect of different N application strategies on garlic yield and quality. The experiment was conducted in the field using garlic cv. Chonan and four N fertilization strategies (T1, N fertilizer applied at 15-day intervals; T2, N fertilizer applied before and after clove differentiation; T3, N fertilizer applied before clove differentiation; and T4, N fertilizer applied after clove differentiation). All treatments received the same N rate (210 kg ha-1). A single N application before clove differentiation (T3) favored lateral shoot growth, resulting in the highest incidence of this defect (11.66%). The other treatments did not differ in lateral shoot incidence. Four classes (3–6) of bulb diameter were observed, with treatments ranked in decreasing order as T2 > T1 > T3 > T4. There were no significant differences in garlic yield between single N application treatments (T3 and T4). However, garlic yield differed by 73% between T1 (13,329 kg ha-1) and T4 (7,679 kg ha-1), by 55.31% between T2 (11,927 kg ha-1) and T4, and by 36% between T1 and T3 (9,783 kg ha-1). These results indicate that two N fertilization strategies can be adopted in high-quality garlic production: fortnightly N fertilization or split N application before and after clove differentiation. A single N application is not recommended, regardless of application timing, as it promotes lateral shoot growth and reduces garlic quality and yield.